Formation and application of boron thin film prepared by ion and vapor deposition method. Ion jochaku usumaku keiseiho (IVD ho) ni yoru chikka hoso (BN) usumaku no keisei to oyo - "Nishiyama, S"; "Ogata, K"; "Kuboshima, R"; "Doi, A"; "Suzuki, Y [Nisshin Electric Co. Ltd., Kyoto (Japan)]" (1993)
Formation of boron nitride (BN) thin films by ion and vapor deposition (IVD) method was reported together with its application to cutting tools to enhance their wear resistances. B was deposited on Si(100) substrates while evaporating a boron material by electron beam heating, and the BN thin films were formed by simultaneous N ion bombardment onto the B-deposited films. The B/N composition ratio of the BN films could be controlled with the arrival numbers of B atoms and N ions (B/N transport ratio) to substrates, and the crystallinity and phases of the BN films also with deposition conditions. As a result, the cubic phase BN (c-BN) was formed by IVD method which was the second in hardness after diamond and stronger than diamond against corrosion by steel at high temperature. In addition, the WC cutting tools with the highly adhesive BN film formed by high-energy IVD and the extremely hard BN film by subsequent low-energy IVD, showed an excellent wear resistance several times as high as TiN tools with a coated film 3 times as thick as the BN film. 4 refs., 10 figs., 1 tab.
Keywords: "36 MATERIALS SCIENCE"; "43 PARTICLE ACCELERATORS"; "BORON NITRIDES"; "CHEMICAL PREPARATION"; "THIN FILMS"; "WEAR RESISTANCE"; "ELECTRON BEAM INJECTION"; "HEATING"; "VAPOR DEPOSITED COATINGS"; "ION BEAMS"; "CORROSION"; "CRYSTALLIZATION"; "CUTTING TOOLS"; "DIAMONDS"; "SILICON"; "STEELS"; "SUBSTRATES"; "TUNGSTEN CARBIDES"; "ALLOYS"; "BEAM INJECTION"; "BEAMS"; "BORON COMPOUNDS"; "CARBIDES"; "CARBON"; "CARBON COMPOUNDS"; "CHEMICAL REACTIONS"; "COATINGS"; "ELEMENTAL MINERALS"; "ELEMENTS"; "FILMS"; "IRON ALLOYS"; "IRON BASE ALLOYS"; "MECHANICAL PROPERTIES"; "MINERALS"; "NITRIDES"; "NITROGEN COMPOUNDS"; "NONMETALS"; "PHASE TRANSFORMATIONS"; "PNICTIDES"; "REFRACTORY METAL COMPOUNDS"; "SEMIMETALS"; "SYNTHESIS"; "TOOLS"; "TRANSITION ELEMENT COMPOUNDS"; "TUNGSTEN COMPOUNDS"; "360201* - Ceramics, Cermets, & Refractories- Preparation & Fabrication"; "430100 - Particle Accelerators- Design, Development, & Operation"